ANALYZING THE CORRELATION OF ORAL EXAMINATION WITH SOCA AND WRITTEN EXAMINATION USING MCQ ON MEDICAL STUDENTS - Ami Febriza; Anni Fitria (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2022)
Background: An oral examination is a method to assess where student responds to one or more examiners’ questions. This method has been used in clinical examination for a long time. Students’ Oral Case Analysis (SOCA) is one of the oral examinations usually used in academic assessments for medical students. It has proven its ability to improve students' critical thinking, motivation, and capability in analyzing a clinical case. On the other hand, written examination using Multiple-Choice Questions (MCQ) has proven to be able to give a brief description of cognitive abilities.Aim: This study aims to analyze the correlation between the results from oral examination using SOCA and MCQ test results of undergraduate medical students.Case discussion: It was a cross-sectional study with 143 students as respondents. SOCA assessment scores were collected to evaluate students' analytical skills after the tutorial. MCQ examination scores were calculated from the final test, consisting of 100 questions related to the Cardiovascular course. Our results stated that the average score from SOCA score was higher than the MCQ test. A significant linear association was found between SOCA and MCQ test with p < 0.005.Conclusion: The significant association between the findings of the SOCA and MCQ indicates that SOCA could predict the MCQ test results.